DESCRIPTION OF THE METHODOLOGICAL SIGNIFICANCE OF ACCULTURATION STRATEGIES. (Conference Zone, 2022)
Acculturation is the process of changing the material culture, customs, and beliefs that result from the direct interaction and interaction of different socio-cultural systems. Acculturation is based on communicative processes. Just as ethnic minorities acquire their cultural characteristics as a result of their interactions with one another, ethnic minorities also learn about new cultural contexts and acquire new skills through communication..